Research Note: Novel reassortant avian influenza A(H9N2) Viruses in Wild Birds in Shanghai, China, 2020–2023 - Jie Hu; Yuting Xu; Min Ma; Chenyao Zhao; Yue Yuan; Guimei He (Poultry Science)
The H9N2 subtype of avian influenza virus poses significant challenges to global poultry and human health. During the active surveillance of avian influenza virus in wild birds in Shanghai from 2020 to 2023, a total of nine H9N2 viruses were identified. To better understand the genetic characteristics of these H9N2 viruses in Shanghai, the whole genome sequences were analyzed. Phylogenetical analysis showed that the nine H9N2 viruses have undergone complicated reassortment with waterfowl viruses along the East Asian-Australasian flyways. The nine H9N2 viruses were classified into seven genotypes, and some of them could contribute internal genes to recently circulating HPAI A(H5N8) and A(H5N1) viruses of clade 2.3.4.4b. These results highlight the importance of active surveillance of AIVs in wild birds to comprehend viral ecology and evaluate potential transmission risk in poultry and humans.